The Excavations at Sakce Gözü - du Plat Taylor, J.
Preface — Reasons for the 1949 Excavations at Coba Hüyük — Summary of the 1949 Excavations — Mounds in the Neighbourhood of Gazianteb — Geographical Position of Sakce Gözü — History of the Region — Stratification of the Site — Pottery — Small Objects — Flint and Obsidian Industry.